Lepidopteran pheromones as potential tools for pest insect control in the Arecaceae family (Research, Society and Development, 2023)
Lepidoptera is the second larger order of Insecta Class. Lepidopteran which feed of species of the Arecaceae family are notorious for the damage they cause, attacking a range from seedlings to the fruit. There are several control methods used against these pest insets, and among them, chemical pesticides are the most explored. Biological and mechanical control are also relevant, but they require a large number of trained workers. Behaviour modulation through chemical communication, using pheromones, stands out with a great potential to sustainably control insect populations. Pheromones have already been identified in lepidopteran pest which infest Arecaceae plants, they are mainly female-produced compounds, and belong to the sexual and contact types. The majority of pheromone compounds identified to this date are classified as Types I and II (unsaturated C10–C18 alcohols and their derivatives; and unsaturated C17–C25 hydrocarbons and their epoxides, respectively) with rare occurrences of Types 0 (short-chain secondary alcohols) and 3 (methyl-branched structures). Considering the vast quantity of lepidopteran species that attack this family and the economic impacts they generate, the present work aggregates the current knowledge on pheromones used the Integrated Pest Management of lepidopteran insects that damage palm plant species, and discusses both the compounds already applied in the field and the promising one that must yet to be tested.